The Relationship Between Knowledge and Prevention Behavior Dengue Hemorrhagic Fever in Ketapang Community South Lampung in 2024 - Septegi, Nigi; Arisandi, William; Hermawan, Nur Sefa Arief (PROMOTOR, 2025)
The South Lampung Health Office recorded 17 cases of DHF in Ketapang sub-district in January 2024, making it the sub-district with the highest number of cases. This study aimed to determine the relationship between community knowledge and DHF prevention behavior in Ketapang. Thissstudy aims to explore the relationship between knowledge and behavior of DHF prevention, and to measure the level of knowledge and behavior of DHF prevention in Ketapang community in 2024. The method used was quantitative with a cross-sectional design. The research sample consisted of 66 respondents who were DHF patients. Data were collected through questionnaires and analyzed using the chi-square test. Results showed a p-value of 0.000 <0.05, indicating a significant association between knowledge and preventive behavior, with an OR of 72. Respondents with less knowledge had a 72 times greater risk of exhibiting inadequate preventive behavior.